Advanced hydrogen evolution electrocatalysts promising sustainable hydrogen and chlor-alkali co-production. Issue 12 (17th November 2021) - Zhang, Lu-Nan; Li, Rui; Zang, Hong-Ying; Tan, Hua-Qiao; Kang, Zhen-Hui; Wang, Yong-Hui; Li, Yang-Guang
Abstract : The joint development of electrocatalytic hydrogen evolution and the chlor-alkali industry are proposed clearly for the first time, and the recent progress of HER electrocatalysts and engineering issues in this field have been reviewed. Abstract : Advanced hydrogen evolution reaction (HER) electrocatalysts matching with the chlor-alkali reaction serve as a vital link to realize the cost-effective and environmentally-benign co-production of hydrogen and chlor-alkali. The core problem in this field is to design and fabricate HER electrocatalysts with high activity and stability under the harsh conditions of chlor-alkali electrolysis. This review highlights the scientific, technical, and engineering advances and challenges in this co-production of hydrogen and chlor-alkali. In detail, the working mechanism and performance test criteria of HER electrocatalysts in chlor-alkali condition are provided. Recently developed HER electrocatalysts that can work in chlor-alkali electrolysis are summarized, with a special emphasis on the relationship between their structure and electrolytic properties. Simultaneously, the latest progress in the technology and engineering of the co-production process is also listed. Finally, the opportunities and the way forward for hydrogen and chlor-alkali co-production are also discussed.